Actor Networking in Forest Fires Mitigation, Ogan Komering Ilir District, South Sumatra Province, Indonesia - Alamsyah Alamsyah; Ardiyan Saptawan; Ermanovida Ermanovida; Indra Yustian (Magister Administrasi Publik, 2019)
Forest fire is a seasonal environmental problem in Indonesia. The Government of Indonesia has introduced a new policy that promotes a networking approach. This paper attempts to analyze the existing networks that emerge during the process of forest fire prevention/mitigation in Ogan Komering Ilir (OKI) District. Drawing on empirical research using Social Network Analysis (SNA), we identify various actors participating in forest fire governance. The local government has promoted the principle of voluntary civil society and plantation corporation participation in the networks, which, however, based on findings does not seem to be effective. Our findings show that mitigation of forest fires in OKI District is plagued by low cohesiveness. The prominent role of the police in the network underscores the approach that the local government is using to tackle forest fires, which is, that it is a security problem and not as a disaster that requires intensive collaboration among multi-stakeholders. To that end, based on the research results, policy recommendations include, the need for the Central Government to establish a ‘stick and carrots’ mechanism for the local government to foster the adoption of collaborative forest fires mitigation management; the need for the local government, especially the provincial government and the district government, to reduce the role of the police while at the same time strengthen the role of non-state actors in forest fire mitigation; the need for the central and the local government to strengthen the capability of civil servants to work under the collaborative ecosystem through systematic learning.